Series analyses and quality specifications required for monitoring over time - Groth, T. (Scandinavian journal of clinical and laboratory investigation, 1999)
General specifications of analytical goals for biochemical monitoring have been proposed based on biological within-subject variation. As a complement to this strategy for general global quality requirements there is also a need for other methods and approaches to set more optimal requirements in specific monitoring situations, i.e. application of systems and sensitivity analysis using (i) rules for propagation of errors (uncertainty) in simple algebraic/statistical transformations of laboratory results; (ii) biochemical/pathophysiological simulation models; and (iii) formalized descriptions of clinical classification and decision support processes. The possible gain in medical outcome by improving analytical and preanalytical quality should then be related to the often more important aspects of selection and combination of ?tests?, period and frequency of sampling/measurement, and the use of correct conceptual and computational models for transformation of data.